Walter B. Wriston '41 - Smith, Nancy (Tufts Archival Research Center, 2007)
This document was created from the article, "Walter B. Wriston '41," written by Nancy Smith for the Fall 1985 edition of the "Wesleyan: The Wesleyan University Alumnus." The original article is located in MS134.003.025.00007.